2011
DOI: 10.1089/jwh.2010.2675
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Posttraumatic Stress Disorder with Fast Food and Soda Consumption and Unhealthy Weight Loss Behaviors Among Young Women

Abstract: Objective: This study examines the association of posttraumatic stress disorder (PTSD) symptoms with fast food and soda consumption, unhealthy dieting behaviors, and body mass index (BMI) in a group of young women. Methods: This study was conducted on cross-sectional data gathered from 3181 females 16-24 years of age attending five publicly funded clinics in Texas. The associations among PTSD, fast food consumption frequency, soda consumption frequency, unhealthy dieting behaviors, and BMI were examined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 28 publications
4
63
3
Order By: Relevance
“…Eating can therefore result in a temporarily elevated mood and can create a behavioral cycle where food is consumed to control feelings of sadness [19•], as is evidenced by work focused on the role of serotonin and dopamine playing a critical role in eating behavior and mood regulation [38]. Recent studies have also suggested PTSD is associated with physical inactivity [39], increased consumption of unhealthy foods and beverages [40], or generally dysregulated food intake related to dependence on activation of the brain reward system [31]. In addition, dysregulated neuroendocrine function, including enhanced negative feedback sensitivity of glucocorticoid receptors, blunted cortisol levels, and exaggerated catecholamine responses to trauma-related stimuli have all been found in adults diagnosed with PTSD [40].…”
Section: Obesity and Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Eating can therefore result in a temporarily elevated mood and can create a behavioral cycle where food is consumed to control feelings of sadness [19•], as is evidenced by work focused on the role of serotonin and dopamine playing a critical role in eating behavior and mood regulation [38]. Recent studies have also suggested PTSD is associated with physical inactivity [39], increased consumption of unhealthy foods and beverages [40], or generally dysregulated food intake related to dependence on activation of the brain reward system [31]. In addition, dysregulated neuroendocrine function, including enhanced negative feedback sensitivity of glucocorticoid receptors, blunted cortisol levels, and exaggerated catecholamine responses to trauma-related stimuli have all been found in adults diagnosed with PTSD [40].…”
Section: Obesity and Ptsdmentioning
confidence: 99%
“…Recent studies have also suggested PTSD is associated with physical inactivity [39], increased consumption of unhealthy foods and beverages [40], or generally dysregulated food intake related to dependence on activation of the brain reward system [31]. In addition, dysregulated neuroendocrine function, including enhanced negative feedback sensitivity of glucocorticoid receptors, blunted cortisol levels, and exaggerated catecholamine responses to trauma-related stimuli have all been found in adults diagnosed with PTSD [40]. An elevated waist circumference is also linked to increased cortisol, a stress hormone that is elevated in both acute and chronic stress [41].…”
Section: Obesity and Ptsdmentioning
confidence: 99%
“…To our knowledge the current literature on this topic is limited to a handful of studies. These include two studies on PTSD and emotional eating (24; 25) (one showing a positive finding, the other null), two studies showing PTSD symptoms to be associated with food addiction (26; 27), and four studies finding greater intake of unhealthy foods and/or lower intake of healthy foods among those with PTSD (2830). One study of earthquake survivors found that meeting PTSD diagnostic criteria was associated with increased craving for sweets or carbohydrates, as well as both increases and decreases in appetite (31).…”
Section: Introductionmentioning
confidence: 99%
“…Trauma's connection with addiction (Hien, Cohen, & Campbell, 2005) and eating disorders (Brewerton, 2007;Grilo et al, 2006;Gunstad et al, 2006;Gustafson & Sarwer, 2004;Hirth, Rahman, & Berenson, 2011;Noll, Zeller, Trickett, & Putnam, 2007) has been documented. In practice, trauma is often unrecognized, although studies have linked PTSD and obesity (Vieweg et al, 2006).…”
Section: Trauma At the Root Of Compulsive Overeatingmentioning
confidence: 99%